Cooperation or rivalry? Impact of alternative development pathways on India's long-term electricity generation and associated water demands. (1st February 2020) - Chaturvedi, Vaibhav; Koti, Poonam Nagar; Sugam, Rudresh; Neog, Kangkanika; Hejazi, Mohamad
Abstract: The world has witnessed a paradigm shift in the last decade in the way countries engage with each other. A cooperation based international paradigm is being challenged by countries engaging in rivalry with each other, motivated by their national interests. The developmental pathway the world charts in the future is going to be path defining for global energy and emissions use. India, expected to play a critical role in the global energy and emissions debate, would continue to impact and be impacted by these pathways. In India specific literature, however, little attention has been paid to development pathways related uncertainties and their impact on India's energy and resource futures. We seek to address this gap by modelling India's electricity futures and associated water demands under different development pathways. Our analysis shows that alternative development pathways would have significantly different implications for the energy access and equity, electricity generation mix, associated water withdrawals, and carbon dioxide emissions in India. We conclude by arguing that energy, emissions and water policies should be conceived with an explicit understanding of uncertainties related to potential development pathways that the world and India can chart. Highlights: Development pathways would have critical implications for India's resource policy. These imply vastly different states of electricity, water and emissions futures. Resource policy should explicitly consider implications of development pathways. India needs to start considering dry cooling seriously as an adaptation option. We also present an India specific dataset of water coefficients for power generation.